STUDI EMPIRIS PENGARUH EARNINGS DAN CASH FLOWS TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAM JAKARTA ISLAMIC INDEKS (JII) - Tito Marta Sugema Dasuki (MAKSI, 2015)
The purpose of this study is to test the ability of earnings information, thecomponent of earning, and cash flows affected stock price. This research is conducted byusing the sample of firms that included the Jakarta Islamic Index (JII). Analysis methodthat used in this research is quantitative method with multiple regression. Samplingmethod that used is purposive sampling.These results indicate that earnings have a significant effect on stock pricesbecause of the tendency of investors to invest in stocks that have huge profits while thetotal cash flow has negative effect on stock prices. Stock price will remain increase asinvestors still believe that the activities of the company still running properly and safelyduring the crises. This is because the company could still pays the debts, pays dividendsand keeps doing investment.Key Word: Earning, Cash Flows, Stock Price, Regression.